MENINGKATKAN MOTORIK HALUS ANAK USIA 4-5 TAHUN MELALUI KEGIATAN MERONCE DI KELOMPOK A TK BHAYANGKARI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Royana, Yuni; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The background of this research is underdeveloped fine motor skills of children optimally among children may not be able: to perform manipulative movement to generate a form by using various media and express themselves with the work of art using various media. Therefore, researchers make improvements and optimize the fine motor skills of children according to age perkembangann level. The purpose of the implementation of this study was to determine the development of fine motor meronce activities, to determine how teachers implement meronce learning through activities that children can be improved fine motor, to know meronce activities can improve fine motor skills, and to determine the height increase fine motor skills through activities meronce children aged 4-5 years in group A kindergarten Bhayangkari District of Bangko Rokan Hilir. This research is a classroom action research conducted in two cycles. In one cycle there are three meetings. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 10 children consisting of 4 boys and 6 girls. Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 29.20%, the first cycle to the second cycle of 51.10%, and increased from the prior cycle to cycle II of 95.3%. From the results of these studies concluded that through meronce activity can improve fine motor skills of children aged 4-5 years in kindergarten Bhayangkari District of Bangko Rokan Hilir.Keyword: Meronce, Fine Motor, Children Aged 4-5 Years